Understanding skin colour: Exploring colourism and its articulation among black and coloured students - Mbatha, Slindile (Department of Psychology, 2017)
While international scholars have increasingly drawn attention to colourism as a social phenomenon, South Africa has yet to understand its various expressions in the wake of a history of apartheid. Colourism can be described as "prejudicial treatment of individuals based on varying degrees of skin colour." This has significant implications for people of colour, who are often targets of racism, but also perpetrators of skin tone discrimination among their own racial group. The main objective of this study was twofold: to enquire about the existence of colourism, and to determine how it may possibly articulate itself as an everyday phenomenon among students. A sample of black and coloured students were drawn from the University of Cape Town student population. Qualitative focus group interviews were conducted to collect all necessary data. The results indicated the existence of colourism in the lives of students including their relationships with family members, friends, potential intimate partners, and in their wider societal context. A thematic analysis revealed four main themes: a) Racial identity formation; b) Skin tone valuations and their influence in the colourism hierarchy; c) Gendered articulations of colourism; and d) Trauma and its effect on the expression of colourism. Racial identity formed an important part of how students situated themselves positively or negatively in the historical and present day context of South Africa. Skin tone valuations meant that greater value was often placed on light skin as an attribute of beauty, wealth and intelligence. However, this was mediated by gender such that the value placed on light and dark skin was often determined by gender. One crucial observation was the pervasive nature of cultural trauma in and through experiences of colourism. Through a process of symbolic violence, colourism was understood as internalised racism which becomes a weapon wielded by black and coloured individuals against themselves. As such, inherited racist beliefs about the inferiority of darker skin, and superiority of lighter skin have been internalised, even among a post-apartheid generation of youth.